DUPLICITY AMONG RR LYRAE TYPE-STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
On the basis of the analysis of small amplitude 0-C variations, seven RR Lyrae variables are detected as possible binaries. It appears, that each one of these has probably a close companion. By using a proximate iterative algorithm, some parameters of their orbits were estimated. An evolutionary status of these stars are considered.